Molecular characterization of endometrial cancer and therapeutic implications. Issue 1 (February 2019) - Chang, Zenas; Talukdar, Shobhana; Mullany, Sally A.; Winterhoff, Boris
Abstract : Purpose of review: The present article reviews genomic subtyping of endometrial carcinoma and new molecular markers with therapeutic and prognostic implications. Recent findings: Endometrial cancer has historically been classified through histology into endometrioid (type 1) and nonendometrioid (type II, mainly serous) subtypes. Molecular classification through genomic analysis now allows for a major advance in characterization; four distinct subgroups have been identified: polymerase ε (POLE) ultramutated, microsatellite unstable, copy number low/microsatellite stable, and copy number high/'serous-like'. These subtypes have prognostic implications and may aid in the identification of early-stage patients who are at high risk for recurrence. Through analysis of surrogate markers (POLE, MSI, and p53) and other validated molecular alterations (L1CAM), it may be possible to obtain an integrated molecular risk profile. Ongoing studies are utilizing this risk profile in order to identify patients who may benefit from additional treatment for early-stage disease. Summary: Molecular characterization of endometrial cancer into subgroups has prognostic and therapeutic implications. Further development of an integrated molecular risk profile may identify patients who could benefit from additional treatment because of a higher risk of recurrence.